Transparência e qualidade da informação pública: uma análise sob a perspectiva do cidadão - Nicolau, Amanda Martins (2024)
Information and communication technologies have enabled significant advancements in advertising and the transparency of actions within the scope of public management. However, to foster social control of public management, it is necessary for the information provided to society to be of good quality. This research evaluates the level of quality of information on the portal of transparency of the Brazilian Federal Government from the perspective of citizens. The theoretical framework of this work addresses the theme of social control in Brazil, transparency and access to public information, and information quality aiming to identify elements for building a model based on the PSP/IQ (Model as the Product and Service Performance Model for Information Quality) proposed by Kahn, Strong, and Wang (2002) and the AIMQ research model (Methodology for Information Quality Assessment) by Lee et al. (2002). This allowed the construction of a questionnaire with 28 items distributed across the following dimensions: reliability, relevance, presentation, timeliness, completeness, usefulness, comprehensibility, and interpretability, assessed through an 11-point Likert scale. The chosen profile for questionnaire application was Brazilian citizens. Data collection was conducted using the Google research management application, Google Forms, and disseminated through social networks such as Instagram and WhatsApp, email, as well as in the academic community of various Brazilian universities and also in institutional emails of companies and public bodies. The survey had 240 respondents and obtained 217 valid responses. The analysis of the results was performed using the coefficient of multiple regression to evaluate the relationship of each independent variable with the dependent variable. The model proposed in this research showed convergent validity, internal consistency, and discriminant validity. The results of this sample suggest that 73.9% of the dependent variable, information quality, is explained by the following independent variables proposed in the model: completeness, usefulness, comprehensibility, and interpretability. The quality of information published on the portal of transparency of the federal government averaged 7.11. This research stands out for presenting an adapted model capable of measuring the quality of public information provided to the population, providing information producers with the opportunity to understand users' perspective regarding the usefulness of the information offered. Furthermore, it discusses the importance of advertising government actions regarding public matters and the need for the population to be involved in this process of monitoring and controlling these actions, emphasizing the importance of measuring the quality of information provided by public transparency portals, highlighting that, although it is difficult to measure the quality of information from the citizen's perspective, it is essential for the effectiveness of transparency policies. Currently, public information portals are mainly evaluated by checklists that measure transparency based on the disclosure of specific information. Research like this can contribute to the development of new measurement methods, promoting the discussion of methods aimed not only at evaluating information disclosure but also the quality perceived by users in order to provide improvements in public transparency policies.